2019
DOI: 10.3390/su11195445
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perception and Drivers of Membership in Rice Production Community Enterprises: Evidence from the Central Region, Thailand

Abstract: In rapidly developing economies such as Thailand, farmers face multiple challenges preventing them from improving their livelihoods, and are therefore reverting to collective action as a means to overcome those obstacles. Community enterprises (CEs) have recently emerged as a new form of such collective action, yet there is limited evidence regarding farmers’ perception of rice production CEs (RPCEs) and the specific factors influencing their decision to join. In order to fill this gap, primary data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 56 publications
(62 reference statements)
2
34
0
Order By: Relevance
“…With regard to the impact of income on the probability of farmers facing agricultural production barriers, the results suggest that off-farm income may ensure cash flow and decrease income fluctuations. As a survival strategy, farmers often seek to diversify their sources of income and use other strategies to stabilise their earnings through off-farm activities [15,16,17] Previous research by [18] analysing the warehouse receipt system in Cianjur and Subang District also showed that income had positive effects on adoption of agricultural innovations. The results also confirm the importance of farming experience.…”
Section: Production and Incomementioning
confidence: 99%
“…With regard to the impact of income on the probability of farmers facing agricultural production barriers, the results suggest that off-farm income may ensure cash flow and decrease income fluctuations. As a survival strategy, farmers often seek to diversify their sources of income and use other strategies to stabilise their earnings through off-farm activities [15,16,17] Previous research by [18] analysing the warehouse receipt system in Cianjur and Subang District also showed that income had positive effects on adoption of agricultural innovations. The results also confirm the importance of farming experience.…”
Section: Production and Incomementioning
confidence: 99%
“…Farm size is expected to influence the ageing workforce negatively. Existing research revealed that the ageing agricultural workforce negatively impacts the effective use of land resources, food security, and agricultural modernisation (Apipoonyanon et al, 2020;He, 2013), however it can have a positive effect on the perception of rice production enterprises (Petcho et al, 2019).…”
Section: Agricultural Variablesmentioning
confidence: 99%
“…The ageing population and shifting occupational patterns have been integrated and linked to the development of economic, social and environmental aspects. Despite this and a number of existing policies and strategies, the agricultural labour force continues to decline (Apipoonyanon et al, 2020;Naipinit et al, 2014;Petcho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Specific challenges include climate variability, limited access to technology, lack of irrigation, degrading soil fertility, an ageing farmer population resulting in labour shortage, and price fluctuations (Dang et al, 2014). Despite the Green Revolution and subsequent technological advances, weather and climate remain the key factors determining agricultural productivity throughout Asia (Petcho et al, 2019; Tsusaka and Otsuka, 2013). Sub-optimal agricultural production can have significant profound effects on the composition of agricultural value chains, market access opportunities for small-scale farmers, and their collective organisation (Petcho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the Green Revolution and subsequent technological advances, weather and climate remain the key factors determining agricultural productivity throughout Asia (Petcho et al, 2019; Tsusaka and Otsuka, 2013). Sub-optimal agricultural production can have significant profound effects on the composition of agricultural value chains, market access opportunities for small-scale farmers, and their collective organisation (Petcho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%